Strategies and indicators to address health equity in health service and delivery systems: a scoping review protocol. Issue 1 (9th January 2022) - Brushett, Sara; Caldwell, Hilary A.T.; Cameron, Emma Stirling; Carrea, Cecilia; Embrett, Mark; Fierlbeck, Katherine; Hajizadeh, Mohammad; Kirk, Sara F.L.; Rothfus, Melissa; Sampalli, Tara; Sim, Meaghan
ABSTRACT: Objective: The purpose of this review is to describe how health service and delivery systems support health equity, and to identify strategies and indicators being used to measure health equity. Introduction: It is widely acknowledged that a population health and equity approach is needed to improve the overall health of the population. The health service and delivery system plays an important role in this approach. Despite this, system transformation to address health inequities has been slow. This is due, in part, to the lack of evidence-based guidance on how health service and delivery systems can address and measure health equity integration. Most studies focus on health equity integration in the public health sector at a provincial or national level, but less is known about integration within the health service and delivery system. More information is needed to understand how that transformation is occurring, or could occur, to make a meaningful contribution toward improving population health outcomes. Inclusion criteria: This scoping review will identify studies that describe the strategies and indicators that health service and delivery systems are using to integrate health equity and how progress is measured. Evidence from qualitative, quantitative, mixed method studies, and gray literature will be included. Methods: This review will be conducted in accordance with JBI methodology for scoping reviews. A comprehensive search strategy, developed with a librarian scientist, will be used to identify relevant sources. Titles, abstracts, and full texts will be evaluated against inclusion criteria. Information will be extracted by two independent reviewers. Data will be synthesized and presented narratively, with tables and figures where appropriate.